The Effect Of Innovation Product, Service Quality To Customer Satisfaction And Customer Loyalty Of Banco Nacional De Comercio Timor-Leste/BNCTL Dili - Sanzinha dos Santos Branca; Luh Komang Chandra Dewi; Augusto da Conceição Soares (ABM: International Journal of Administration, Business and Management, 2020)
The objective of this thesis is to analyze and explain: 1) The effect of product innovation to customers’ satisfaction, 2) The effect of services quality to customers’ satisfaction, 3) The effect of products’ innovation to customers’ loyalty. 4) The effect of services quality to customers’ Loyalty. And 5) The Effect of customers’ satisfaction to customers’ loyalty. The data collection in this research through distribution of questioner to customers of BNCTL Bank in Dili. The sampling technique used is non-probability sampling with purposive sampling technique, total of 80 respondents were chosen. The data is analyzed by using descriptive statistic and inferential in path analysis With SMARTPLS. The result of the research shows that innovation product and service quality have positive and significant influence to customer satisfaction and customer’s loyalty of Bank BCNTL in Dili. In addition, customer satisfaction have positive and significant influences to customer’s loyalty. Therefore, the more BNCTL banks sold their innovating products according to the needs and desires of customers by paying attention to the three indicators, the customer satisfaction and loyalty will also increase. In addition, the better quality of service received by the customer, it will further increase the satisfaction and loyalty of customers of the BNCTL bank in Dili. Therefore, it is hoped that the bank will always pay attention to product innovations that are in accordance with the needs and desires of customers So that satisfaction and loyalty are also increases. Keywords: Product Innovation, Service of quality, Satisfaction and Customer Loyalty.